2014
DOI: 10.2172/1166986
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Solar Photovoltaic Pricing: The Role of Market Structure, Technology, and Policy

Abstract: Solar photovoltaic (PV) system prices in the United States display considerable heterogeneity both across geographic locations and within a given location. Such heterogeneity may arise due to state and federal policies, differences in market structure, and other factors that influence demand and costs. This paper examines the relative importance of such factors on equilibrium solar PV system prices in the United States using a detailed dataset of roughly 100,000 recent residential and small commercial installa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
75
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(87 citation statements)
references
References 42 publications
10
75
2
Order By: Relevance
“…Follow-up work by Nemet et al (2016b) found that many of the same factors appear to drive low-priced systems to be even lower priced. Gillingham et al (2014) examined a broad range of potential drivers for PV pricing variability among residential systems installed during 2010 to 2012. Of the various factors considered, the single-largest contributor was system size ($1.5/W effect).…”
Section: Text Box 5 Findings From Recent In-depth Analyses Of Pv Primentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up work by Nemet et al (2016b) found that many of the same factors appear to drive low-priced systems to be even lower priced. Gillingham et al (2014) examined a broad range of potential drivers for PV pricing variability among residential systems installed during 2010 to 2012. Of the various factors considered, the single-largest contributor was system size ($1.5/W effect).…”
Section: Text Box 5 Findings From Recent In-depth Analyses Of Pv Primentioning
confidence: 99%
“…High-volume installers (as well as smaller installers with a dominant presence in particular locations) may also possess a degree of market power and/or reputational advantages, enabling higher pricing. These competing dynamics have, to varying degrees, been substantiated in Gillingham et al (2014) …”
mentioning
confidence: 99%
“…It is also conceivable that high-volume installers (or, for that matter, smaller installers with a dominant presence in particular locations) may enjoy a certain degree of market power, permitting higher pricing. These competing hypotheses have, to varying degrees, been substantiated in Gillingham et al (2014) and are a subject of continuing investigation by LBNL and its collaborators in the study series referenced in Text Box 4.…”
Section: Notes: Each Line Includes Only Installers That Completed At mentioning
confidence: 99%
“…43 Gillingham et al (2014) find that average price per kW of capacity falls with capacity out to about 8kW The impact of annual electricity usage and household income bracket are both very statistically and economically significant. A one standard deviation increase in annual consumption raises the price of the system by about $1400, or about 4% at the mean.…”
mentioning
confidence: 97%
“…40 Gillingham et al (2014) estimate a system pricing equation using data from many states and incorporating many more variables, including measures of supply side variables on installer competition and experience. Each approach has its advantages.…”
mentioning
confidence: 99%